Fatty fish, hair mercury and cognitive function in Norwegian preschool children: Results from the randomized controlled trial FINS-KIDS. (December 2018) - Kvestad, Ingrid; Vabø, Silje; Kjellevold, Marian; Nøstbakken, Ole Jakob; Midtbø, Lisa Kolden; Hysing, Mari; Markhus, Maria Wik; Madsen, Lise; Handeland, Katina; Graff, Ingvild Eide; Lie, Øyvind; Frøyland, Livar; et al.
Abstract: Background: The toxic effects of prenatal methylmercury (MeHg) include neurological abnormalities and developmental delay of which infants and children are particular susceptible. Studies on the effects of low and moderate exposure show conflicting results. Seafood is the main dietary source of MeHg, but also contributes with nutrients regarded as beneficial for development. Objectives: To measure the change in total hair mercury concentration (THHg) after an intervention of lunch meals with fatty fish or meat in Norwegian preschool children, and to examine the associations between THHg and cognitive function. Methods: Children (n = 232) 4–6 years old were randomized to lunch meals with fatty fish (n = 114) or meat (n = 118) three times a week for 16 weeks. THHg was determined using a Direct Mercury Analyzer, and cognitive function was assessed by the Wechsler Preschool and Primary Intelligence Scale-III (WPPSI-III) pre- and post-intervention. Linear mixed effect models were used to analyze changes in THHg and WPPSI-III scores. Results: The mean (SD) THHg pre-intervention was 0.373 (0.204) mg kg −1 . Children in the fish group had an increase in THHg (change 0.162, 95% CI 0.111, 0.213 mg kg −1 ), whereas children in the meat group had decreased THHg (−0.053, 95% CI −0.103, −0.002 mg kg −1 ). There were no notable associations between THHg and the WPPSI-III raw scores at baseline or after 16 weeks of the fish/meat intervention. Conclusions: Lunch meals including fatty fish led to a significant increase in THHg, but the values remain below the point of departures used for risk assessment by the EFSA, WHO and US-EPA. We observed no associations between THHg and cognitive function. Highlights: A fatty fish intervention increased mercury hair-concentration in preschoolers. Mercury exposure from the intervention was below the tolerable weekly intake. The mercury hair-concentration remained below points of departures shown by EFSA. Mercury hair-concentration was not related to cognition in the preschoolers.